2014
DOI: 10.4052/tigg.26.79
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts and Anti-Glycolipid Antibodies

Abstract: Lipid rafts are dynamic assemblies of glycosphingolipids, cholesterol, and proteins that can be stabilized into platforms in- A. IntroductionLipid rafts are dynamic assemblies of glycosphingolipids, sphingomyelin, cholesterol, and proteins that can be stabilized into platforms involved in the regulation of a number of vital cellular processes (1). Low-density, detergent-resistant membrane fractions can be isolated from cells by sucrose density gradient centrifugation. These membrane fractions are rich in glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Treatment of intact cells with anti-glycosphingolipid monoclonal antibodies can induce transmembrane signaling via specific lipid rafts (17). Therefore, anti-glycosphingolipid mono-clonal antibodies are useful tools for the analysis of heterogeneity in raft signaling (18). We also demonstrated that anti-sulfatide antibody O4 immunoprecipitates sulfatide rafts including Fyn, Lyn and the G protein α subunit in rat primary immature oligodendrocytes (19).…”
Section: B Neuronal Raftsmentioning
confidence: 76%
“…Treatment of intact cells with anti-glycosphingolipid monoclonal antibodies can induce transmembrane signaling via specific lipid rafts (17). Therefore, anti-glycosphingolipid mono-clonal antibodies are useful tools for the analysis of heterogeneity in raft signaling (18). We also demonstrated that anti-sulfatide antibody O4 immunoprecipitates sulfatide rafts including Fyn, Lyn and the G protein α subunit in rat primary immature oligodendrocytes (19).…”
Section: B Neuronal Raftsmentioning
confidence: 76%
“…For example, we can now consider whether NEU1 sialidase contributes to the first step of the tight interactions (44) between T cells and epithelial cells or not. In this regard, it must be important to study the interactions of functional proteins and lipids dynamically in the membrane of the limited part (i.e., lipid raft) from a new point of view(45,46), which may determine the position and function of the proteins. It must be also important to think about the complex formation of the functional proteins with low molecular weight proteins such as tetraspanin.…”
mentioning
confidence: 99%